Advances in planar lipid bilayers and liposomes. - Ottova-Leitmannova, Angelica (Advances in planar lipid bilayers and liposomes ;, 2006)
The lipid bilayer is central to life, as all living organisms possess a lipid bilayer structure, thereby underlying the lipid bilayer principle of biomembranes. The lipid bilayer principle and its applications are the main theme of this new book series. This new series on bilayer lipid membranes (BLMs and liposomes) include invited chapters on a broad range of topics, from theoretical investigations, specific studies, experimental methods, to practical applications. Written for newcomers, experienced scientists, and those who are not familiar with these specific research areas, the Series cove.